Bedeutung der Gesamt-tau- und Phospho-tau-Protein-Liquorspiegel in der Demenzdiagnostik - Hort, Jakub; Vališ, Martin; Waberžinek, Gerhard; Taláb, Radomír; Glossová, Ludmila; Bojar, Martin; Vyhnálek, Martin; Škoda, David; Masopust, Jiří; Štourač, Pavel (Nervenarzt, 2008)
BACKGROUND: The diagnosis of Creutzfeldt-Jakob disease (CJD) is based on typical clinical features and can be supported by detection of 14-3-3 protein in the CSF. The present study suggests the importance of investigating this ratio of total tau protein to phosphorylated tau protein in differentiating CJD from other dementias. Thirty-one patients with Alzheimer's disease (AD) or frontotemporal dementia and four with definitive diagnoses of CJD were included in the study. METHODS AND MATERIAL: Results from baseline investigations were compared with those from an age-matched cognitively controlled group with Bell's palsy. Tau protein, phosphorylated tau protein, and beta amyloid were analyzed using a commercially available enzyme-linked immunosorbent assay; 14-3-3 protein was assessed by Western blotting. RESULTS AND CONCLUSION: A distinctly high proportion of total tau protein to phosphorylated tau protein in CSF was found in all patients diagnosed with CJD, even in those with negative 14-3-3 protein blot results. In contrast, marker analysis in patients with Alzheimer's dementia revealed the highest CSF ratio of beta amyloid to phosphorylated tau protein levels. These proteins are important diagnostic biomarkers for CJD, especially in patients with negative 14-3-3 protein findings.
Keywords: Dementia; 14-3-3 Proteins; diferenciální diagnóza; Female; proteiny 14-3-3; Creutzfeldt-Jakob Syndrome; ženské pohlaví; demence; Reproducibility of Results; lidé; Sensitivity and Specificity; senzitivita a specificita; Diagnosis, Differential; reprodukovatelnost výsledků; Male; fosforylace; Aged; Alzheimer Disease; Creutzfeldtova-Jakobova nemoc; Alzheimerova nemoc; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Phosphorylation; Humans